(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
Background: Reproductive Healthcare Services is a service that contributes to reproductive health and wellbeing through preventing and solving reproductive health problems. Objective of the Study: To find out the reproductive health status and also the service delivery pattern in a rural area. Methodology: It is a cross sectional study done in a village named Kalirbazar, 3km away from the BARD, Comilla, during the period of13th February to 13th March, 2011. Data were collected purposively by Individual interview through a structured questionnaire. A total 30 women of reproductive age group (15-45yrs) were taken. Both adolescent unmarried girls and married women of reproductive age group were included in this study. After collection, data were analyzed, tabulated and presented. Results: Respondents were mostly married( 63%), unmarried 33%; almost all of the women were Muslim (93%) and from low socioeconomic status(77%). Sixty six percent of women got married before 18 yrs of age and 47% were illiterate, more than half of the women (60%) were housewives and 28% dropped out from schools. Forty percent of married women had 2-3 children.Most of the Women had knowledge about contraception, like-OCP (33%), inj. (27%), barrier (17%), female sterilization (06%) and 17% had no knowledge. Among the married women 53% use OCP, 32% injectable contraceptives, 11% sterilization and 04% had vasectomy. Among respondents, 70% had some sorts of menstrual problem, 85% women lacked of antenatal checkup, 95% delivery occurred at home, 90% delivery conducted by local dhai and unexpectedly 73% of women had knowledge of STD/HIV&AIDS. 60% of the women got the information related to reproductive health from relatives and also from media, health care provider. Most of the women (87%) said that whatever the health service status; there were problems in getting the services. Only few of them were satisfied with the services getting either from GO or NGO or from private sector. Almost all the women were buying the reproductive healthcare services (83%). Conclusion: Reproductive health status in the rural area is not at all satisfactory. GO. and NGO often fail to make health services available to the doorstep of the users in the community who are in dire need of it . DOI: http://dx.doi.org/10.3329/bjog.v26i1.13756 Bangladesh J Obstet Gynaecol, 2011; Vol. 26(1) : 27-30